Employees' Improvisational Behavior: Exploring the Role of Leader Grit and Humility. Issue 2 (15th March 2022) - Rego, Arménio; Vitória, Andreia; e Cunha, Miguel Pina; Owens, Bradley P.; Ventura, Ana; Leal, Susana; Valverde, Camilo; Lourenço-Gil, Rui
ABSTRACT: In spite of a growing interest for improvisation in organizations, the microfoundations of improvisation have not been theorized yet. Exploring these microfoundations, we study how employees' psychological capital (PsyCap) acts as a critical cluster of resources to face improvisational challenges and how leaders who convey grit (operationalized as perseverance of effort: Grit-PE), counterbalanced with humility, create conditions to develop those resources. By building upon the conservation of resources and the dual-systems model of self-regulation theories, our empirical studies suggest that the interaction between two leader-conveyed resources (Grit-PE and humility) creates a contextual resource that helps employees develop PsyCap, thus making them more likely to improvise. The positive effect of high Grit-PE in leaders on employees' improvisation materializes mainly when leaders also are humble.